Luteolin Inhibits Human Keratinocyte Activation and Decreases NF-κB Induction That Is Increased in Psoriatic Skin - Weng, Zuyi; Patel, Arti B.; Vasiadi, Magdalini; Therianou, Anastasia; Theoharides, Theoharis C. (PLOS ONE, 2014)
Psoriasis (Ps) is an autoimmune disease characterized by keratinocyte hyperproliferation and chronic inflammation, with increased expression of tumor necrosis factor (TNF) and vascular endothelial growth factor (VEGF). Anti-TNF biologic agents are effective in treating Ps, but are associated with increased risk of infections and blood malignancies. Moreover, keratinocyte hyperproliferation and activation have yet to be addressed. Flavonoids, such as luteolin, are natural compounds with potent anti-inflammatory properties, but their actions on keratinocytes remain unknown. We show that TNF (50 ng/mL) triggers significant production of inflammatory mediators interleukin-6, interleukin-8 and VEGF from both human HaCaT and primary keratinocytes. Pretreatment with the flavonoid luteolin (10–100 µM) significantly inhibits mRNA expression and release of all three mediators in a concentration-dependent manner. More importantly, luteolin decreases TNF-induced phosphorylation, nuclear translocation and DNA binding of the nuclear factor-kappa B (NF-κB) typically involved in inflammatory mediator transcription. We also report that luteolin reduces TNF-induced mRNA expression of two genes (NFKB1 and RELA) encoding two NF-κB subunits (NF-κB p50 and NF-κB p65, respectively). Interestingly, we show that gene expression of RELA is increased in human psoriatic skin. Keratinocyte proliferation, which is a characteristic feature of psoriatic skin, is effectively reduced by luteolin in HaCaT cells, but not in primary keratinocytes. Finally, luteolin does not affect intracellular ATP production or viability. Appropriate formulations of luteolin and related flavones may be promising candidates to be developed into local and systemic treatments for Ps and other inflammatory skin diseases.